2019
DOI: 10.1007/s00259-018-4237-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of (Z)-isomer content on [11C]ABP688 binding potential in humans

Abstract: Purpose: To determine how the low-affinity (Z)-isomer of the radiotracer [ 11 C]ABP688 affects binding potential values in vivo in humans. Methods:High resolution [ 11 C]ABP688 PET scans were acquired on 74 healthy volunteers (25 male, 49 female, mean age 20±3.0). Relative content of (E)-and (Z)-isomer were determined prior to injection using analytical high performance liquid chromatography (rt(E) = 10 minutes, rt(Z) = 8.5 minutes). Mean binding potential (BPND= fND * (Bavail / KD)) values were calculated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Indeed, despite the presence of mGlu5 receptors in the cerebellum, only a negligible fraction specifically binds to the radiotracer [ 58 ], minimizing the likelihood of a bias or difference in cerebellar uptake between our groups. Instead, we recently documented that much of the variability in [ 11 C]ABP688 BP ND [ 59 ] reflects effects of time of day [ 60 ], (Z)- isomer content in the synthesized batch of tracer [ 53 ], and sex [ 54 ]. All three factors were controlled for in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, despite the presence of mGlu5 receptors in the cerebellum, only a negligible fraction specifically binds to the radiotracer [ 58 ], minimizing the likelihood of a bias or difference in cerebellar uptake between our groups. Instead, we recently documented that much of the variability in [ 11 C]ABP688 BP ND [ 59 ] reflects effects of time of day [ 60 ], (Z)- isomer content in the synthesized batch of tracer [ 53 ], and sex [ 54 ]. All three factors were controlled for in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For all ANCOVAs and t -tests, sex, isomer ratio, AUDIT scores, tobacco smoking status and drug use (other than cannabis) were included as covariates. Each of these factors is associated with differences in [ 11 C]ABP688 BP ND [ 22 24 , 26 , 53 , 54 ]. Greenhouse-Geisser corrections were applied when the assumption of sphericity was violated ( p < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…These conditions were validated for a baseline separation of the two isomers, as under our old previously described radiosynthesis method the d.e. of (E) ‐[ 11 C]ABP688 was 84 ± 3.9% . The identity of ( Z )‐ and ( E )‐ABP688 isomers were validated by analysing ABP688 reference standard (ABX, Cat No 3570) with nuclear magnetic resonance (NMR).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, ( E )‐ABP688 has over 20‐fold higher affinity to mGlu5 receptors, and, therefore, the presence of a nearly biologically inactive ( Z )‐isomer decreases the estimates of tracer's in vivo binding potential (BP) in rats . Although some radiosynthesis methods can enhance E / Z ratio to up to 70:1 on average (range: 42:1‐98:1), a human study in our PET center has recently observed that the presence of even modest amounts of ( Z )‐[ 11 C]ABP688 in the final product can reduce estimates of BP ND , where each 1% increase in (Z) ‐isomer content led to 2% and 1% decreases of the minimum and the mean BP ND values in striatum, respectively . These results prompted us to improve the tracer radiosynthesis to provide PET researchers with [ 11 C]ABP688 batches of >99% diastereomeric excess (d.e.).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of a large series of [ 11 C]ABP688 ( 82 ) studies in human subjects showed that the product was not stereochemically pure, but consisted of about 8% ( Z )-isomer [ 172 ], which tended to reduce the magnitude of the BP ND estimate, as had been shown earlier in rat studies [ 173 ]. Presumably, this effect may have accounted for the relatively high 11–21% test-retest variability reported in healthy volunteers [ 174 ].…”
Section: Glutamate Receptorsmentioning
confidence: 97%